A list of big mammals recorded in Quangtri province and their conservation significance - Dang, Nguyen Xuan; Can, Dang Ngoc; Nghia, Nguyen Xuan (Academia Journal of Biology, 2014)
Mammal fauna in Quangtri province was poorly studied. Most of surveys were conducted during period from 2002 to 2007 and concentrated in DaKrong nature reserve (NR) and Bac Huonghoa NR. Totally, 54 species of big mammals belonging to 20 families and 7 orders has been inventoried, of which 49 species with confirmed record and 6 species with temporary record. Number of species recorded for DaKrong PA is 49 species, for Bac Huonghoa PA is 47 species and Legendary Hochiminh trail PA is 25 species. Out of 54 species recorded, 37 species are of high conservation concern, including 30 species enlisted in Red Data Book of Vietnam (2000), 26 species in 2004 IUCN Red List of Threatened Species, 36 species in Governmental Decree 32/2006/ND-CP and 6 species endemic to Indochina. Forest ecosystems of Quangtri province are especially important for conservation of Sao la (Pseudoryx nghetinhensis), white-cheeked gibbon (Nomascus leucogenys), red-shanked douc langur (Pygathrix nemaeus), serow (Naemorhedus sumatraensis), Indochinese striped rabbit (Nesolagus timminsi) and (Trachypithecus laotum hatinhensis).